Effects of substratum, temperature, and treatments to overcome dormancy on the germination of Fimbristylis dichotoma seeds - Martins, Cibele Chalita [UNESP]; Bombonato, Juliana [UNESP]; Marcussi, Fernando [UNESP]; Martins, Dagoberto [UNESP] (Editora Cubo, 2013)
Tall fringe-rush (Fimbristylis dichotoma) is a common weed in wetlands. Knowledge of the physiology of its seed germination can significantly contribute to the development of management strategies. The objective of this study was to determine the best combination of temperature, substratum, and treatments leading to seed dormancy suppression thus enhancing seed germination. In a first phase, seeds were put to germinate under constant temperatures ranging from 15 to 40 °C at 5 °C intervals and alternating temperatures of 15-25, 15-35, and 20-30 °C (8 h of light). The effects were evaluated by means of a germination test carried out in filter paper. In another experiment, the seeds were submitted to the following treatments: 1. seeds immersion in H2 SO4 for 3 min, 2. seeds immersed in H2 O for 15 min, 3. seeds immersed in a 1% KNO3 solution for 15 min, 4. seeds dried at 50 °C for 12 h, and 5. non treated ( check treatment) seeds. The effects in the second experiment were evaluated by means of a germination test carried out in the following substrata: 1. a ready-made substratum (bioplant prata™), 2. soil, and 3. sand. In both experiments, the evaluations were the following: total germination, germination first count (three days), speed of germination index, and mean time for seed germination. The experimental units were distributed in the germination chamber according to a completely random design with four repetitions. The results showed that the best germination result (94%) was attained when the tall fringe-rush seeds were dried for 12 h at 50 °C and put to germinate under either ready-made or soil substrata and under alternate temperatures of either 15-25 or 15-35 °C.

O falso-alecrim-da-praia (Fimbristylis dichotoma) é uma planta daninha comum em áreas úmidas. O conhecimento da ecofisiologia da germinação dessa espécie pode contribuir significativamente para o desenvolvimento de estratégias de manejo. O objetivo deste trabalho foi identificar condições de temperatura, substrato e tratamentos de superação de dormência que favorecem a germinação de sementes dessa espécie. Numa primeira etapa da pesquisa, foi avaliada a germinação das sementes sob temperaturas constantes de 15 a 40 °C, com intervalos de 5 °C, e temperaturas alternadas de 15-25, 15-35 e 20-30 °C (8 h de luz). Numa segunda etapa, foram avaliados os tratamentos de imersão das sementes em H2 SO4 por 3 min; H2 O por 15 min; KNO3 (1%) por 15 min; secagem a 50°C por 12 h, e sementes sem tratamento (testemunha), avaliadas quanto à germinação em substrato industrializado para mudas, terra e areia. Determinaram-se a germinação; a primeira contagem de germinação (sete dias); o índice de velocidade de germinação, e o tempo médio de germinação até 40 dias, avaliado em um delineamento inteiramente casualizado com quatro repetições de 200 sementes. Concluiu-se que a germinação de sementes de falso-alecrim-da-praia deve ser realizada nas temperaturas alternadas de 15-25 e 15-35 °C, em substrato industrializado para mudas ou terra, e após secagem das sementes a 50 °C por 12 h, para a superação da dormência (94% de germinação).
Temperatura, substrato e tratamentos de superação de dormência na germinação de sementes de Fimbristylis dichotoma
Keywords: Ecophysiology; Tall fringe rush; Weed science; Weed; Ecofisiologia; Falso-alecrim-da-praia; Matologia; Planta daninha